2019
DOI: 10.1038/s41467-019-09831-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional cardiac fibroblasts derived from human pluripotent stem cells via second heart field progenitors

Abstract: Cardiac fibroblasts (CFs) play critical roles in heart development, homeostasis, and disease. The limited availability of human CFs from native heart impedes investigations of CF biology and their role in disease. Human pluripotent stem cells (hPSCs) provide a highly renewable and genetically defined cell source, but efficient methods to generate CFs from hPSCs have not been described. Here, we show differentiation of hPSCs using sequential modulation of Wnt and FGF signaling to generate second heart field pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 71 publications
4
132
0
Order By: Relevance
“…However, the optimal fibroblast cell type needed to elicit an adult-like phenotype are cardiac fibroblasts formed via the epithelial-mesenchymal transition (EMT) and originating from epicardial cells. Constructs made with co-cultures of iPSC-CMs and EMT fibroblasts had better systolic and diastolic benchmarks when compared to tissues made from iPSC-CMs and other stromal cells [158]. Likewise, adding endothelial cells and/or smooth muscle cells with the fibroblasts also improves the tissues' phenotype [159,160].…”
Section: Ipsc-cm Maturationmentioning
confidence: 97%
“…However, the optimal fibroblast cell type needed to elicit an adult-like phenotype are cardiac fibroblasts formed via the epithelial-mesenchymal transition (EMT) and originating from epicardial cells. Constructs made with co-cultures of iPSC-CMs and EMT fibroblasts had better systolic and diastolic benchmarks when compared to tissues made from iPSC-CMs and other stromal cells [158]. Likewise, adding endothelial cells and/or smooth muscle cells with the fibroblasts also improves the tissues' phenotype [159,160].…”
Section: Ipsc-cm Maturationmentioning
confidence: 97%
“…CFs, have been increasingly recognised as major players in cardiac development and homeostasis, having a similarly significant effect upon the capacity to build cardiac tissues in the lab. Recently, two independent groups have reported the generation of hPSC-derived CFs, giving also proof of their capacity to affect hPSC-CM function (Zhang H. et al, 2019;Zhang J. et al, 2019). Epicardial cells have similarly been derived, (Witty et al, 2014) demonstrating their ability to increase the therapeutic capacity of hPSC-CMs in vivo (Bargehr et al, 2019).…”
Section: Cellsmentioning
confidence: 99%
“…In a 3D scaffold, mainly, if it is a hydrogel or soft gel with poor compliance than the heart tissue, the fibroblast can act by remodeling the ECM and allowing a more robust gel compaction and remodeling, which results in a better cell-to-cell contact and likely an increase in tissue mechanical properties, thereby enabling the mechanosensing-mediated signaling, which is fundamental for tissue maturation. Interestingly, in a recently published work, the authors reveal a unique gene signature defining specific quiescent CF and showed that co-culture of hPSC-CFs with hPSC-CMs alter the electrophysiological properties of the CMs, as compared with co-culture with dermal fibroblasts, indicating the importance of tissue specificity, and could be used not only to improve the maturation of cultured cells but also to reveal the specific molecular signaling that regulates, and is regulated by, mechanosensing (Zhang et al, 2019). Another important aspect in the generation of functionally 3D cardiac tissue is the perfusion, which allows enough nutrient supply to the cultured cells, and it overall results in better cell survival, cell organization, and tissue compaction (Carrier et al, 2002;Radisic et al, 2008).…”
Section: Mechanosensing In Tissue Regeneration and Modelingmentioning
confidence: 99%